Identification and functional analysis of a novel TRAPPC2 intronic variant in a four-generation Chinese pedigree with SEDT - Lyu, Yongfen; Xu, Wuhen; Xu, Bin; Tang, Xiaojun; Xiao, Man; Lan, Xiaoping; Yang, Yongchen; Song, Xiaozhen; Wu, Shengnan (Frontiers in Genetics, 2026)
BackgroundPathogenic variants in the trafficking protein particle complex subunit 2 (TRAPPC2) gene are known to cause X-linked spondyloepiphyseal dysplasia tarda (X-linked SEDT), a rare hereditary cause of childhood short stature. Genetic diagnosis is critical in early diagnosis and management of the disease. Majority of the pathogenic variants are predicted to cause premature truncation. However, few have been functionally studied. In this study, we reported a Chinese pedigree with multiple affected remarkably short stature males and described the novel variant by in-vitro functional study.MethodsTo complete precise molecular diagnosis and subsequent genetic counseling of a large Chinese pedigree with remarkably short stature. Trio whole exome sequencing was performed on the proband and his parents and phenotype-driven data analysis was conducted. The potentially pathogenic variant was verified by Sanger sequencing in parent-offspring trio and other family members. In vitro experiments involving minigene splicing study and protein expression assay were performed for the potentially disease-causing noncanonical splice variant.ResultsUsing whole exome sequencing, we identified a novel intronic variant, c.94–11C>G, located in intron three of the TRAPPC2 gene. Minigene analysis confirmed that this variant resulted in abnormal splicing, leading to a frameshift insertion of 10 nucleotides and a subsequent loss of TRAPPC2 protein expression. This variant has never been reported.ConclusionOur findings highlight the pathogenic nature of a novel noncanonical splicing variant, thus expanding the genetic spectrum of TRAPPC2-related disorder. Furthermore, this discovery has important implications for genetic counseling, prenatal genetic diagnosis, and follow-up care for affected individuals in this family.